2006
DOI: 10.1074/jbc.m513382200
|View full text |Cite
|
Sign up to set email alerts
|

A Single Chondroitin 6-Sulfate Oligosaccharide Unit at Ser-2730 of Human Thyroglobulin Enhances Hormone Formation and Limits Proteolytic Accessibility at the Carboxyl Terminus

Abstract: We localized the site of type D (chondroitin 6-sulfate) oligosaccharide unit addition to human thyroglobulin (hTg). hTg was chromatographically separated into chondroitin 6-sulfate-containing (hTg-CS) and chondroitin 6-sulfate-devoid (hTg-CS 0 ) molecules on the basis of their D-glucuronic acid content. In an ample number of hTg preparations, the fraction of hTg-CS in total hTg ranged from 32.0 to 71.6%. By exploiting the electrophoretic mobility shift and metachromasia conferred by chondroitin 6-sulfate upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…demonstrated that CS oligosaccharide units are a main source of the molecular microheterogeneity of human Tg. ( 9 ) Thus, our results should be considered to represent the average total sulfation levels of CS in human Tg extracted from normal thyroid and carcinoma tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that CS oligosaccharide units are a main source of the molecular microheterogeneity of human Tg. ( 9 ) Thus, our results should be considered to represent the average total sulfation levels of CS in human Tg extracted from normal thyroid and carcinoma tissues.…”
Section: Discussionmentioning
confidence: 99%
“…( 7 ) Human Tg is unique in that it has O ‐glycosidic‐linked oligosaccharides that have not been found in other animals. ( 8 ) Recently, the CS side chain of Tg was reported to affect the proteolytic accessibility and hormone‐liberating qualities of Tg; ( 9 ) to date, no detailed analysis of CS in carcinoma‐derived Tg has been reported.…”
mentioning
confidence: 99%
“…Intriguingly, the ratio of T 3 and T 4, which is derived from human thyroglobulin, was affected by a CSchain linked onto a subset of the protein. This effect was likely related to the blocking of specific proteolytic cleavage sites (30). Whether CS-modifications influence the processing of the above identified prohormones in a similar way remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Prohormones are known to undergo extensive post-translational modifications, such as phosphorylation, tyrosine sulfation, and glycosylations (30). These modifications may influence the action of proprotein convertases and thereby contribute to the functional processing of the prohormones.…”
Section: Discussionmentioning
confidence: 99%
“…In human TG, the major epitopes for autoimmune thyroid disease-related antibodies involve the surface loop between helices α3(7,8) and α4(7,8), the C-terminal helix α10 and strands β9 and β10, all being located in the C-terminal part of the subunit, suggesting that antibody binding could destabilize or disrupt the dimer [ 50 , 51 ] ( Figure 1 ). In contrast, presence of a bulky chondroitin 6-sulfate oligosaccharide moiety linked downstream to helix α10, and reported to enhance hormone formation and limit proteolytic accessibility of the C-terminus [ 52 ], may contribute to dimer stability ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%